PENGARUH MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) BERBANTU WORD SQUARE TERHADAP HASIL BELAJAR EKONOMI PESERTA DIDIK KELAS X SMA MUHAMMADIYAH 1 BANDAR SRIBHAWONO TAHUN PELAJARAN 2018/2019 - Eva Riska Yunita; Triani Ratnawuri; Meyta Pritandhari (Universitas Muhammadiyah Metro, 2021)
The problem that occurred at SMA Muhammadiyah 1 Bandar Sribhawono is that there are still many learners who have not been able to learn the results of learning economic subjects. To solve the problem, researchers provide one of the learning models that can be applied i.e. model Contextual Teaching and Learning (CTL). The purpose of this research is to know the influence of the Contextual Teaching and Learning (CTL) model of Word square to the outcome of the students ' economic study of class X in SMA Muhammadiyah 1 Bandar Sribhawono Year lesson 2018/2019. This type of research is a quantitative study with the design of experimental Quasi research and using Non-Equivalent Group Design Research design using two classes of experimental and control classes. The sampling techniques used are saturated sampling. This is demonstrated by the test results (pre test) where the < This (0.112 < 2.006) Thitung is received and the H1 is rejected which means there is no difference between the average of learners (pre test) students in the control class with the experimental class. As for after treatment, the student test result (post test) is shown by the value Thitung > This (-2.067 > 2.006) then H0 rejected and H1 accepted. The results showed that there was an influence on Contextual Teaching And Learning (CTL) learning model that helped word square towards economic outcomes of students of class X SMA Muhammadiyah 1 Bandar Sribhawono learning year 2018/2019